Ano pa mga tntxt nya sau? a study of code-switching in text messages - Magno, Francis P.; Laurel, Ma. Milagros C. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2005)
With the prevalent occurrence of multilingualism and with the fact that English is coming into contact with so many languages in the world, code-switching is made possible. Code-switching is most evident in oral interactions. In the past years, however, a new way of communicating emerged as technology advances. Text messaging is a common phenomenon in the Philippines. The Philippines is tagged as the text capital of the world. With its thirty -four million mobile phone owners, the whole archipelago sends at least two hundred million messages a day. Studies show that text messaging has both the characteristics of spoken and written communication. Code-switching is common in oral interactions. This paper assumes that code-switching is also present in text messaging since it has some of the characteristics of oral interaction. The study looks into code-switching in text messages among Filipino text senders. This study looks into the structural patterns of code-switching in text messages as well as the frequency of occurrence of code-switching in text messages. The study has proven that there is a system governing code-switching in text messages. It is not disorganized and that the matrix language of a code-switched utterance can actually be systematically defined.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.